The Effect of Advertising, Perception and Consumer Knowledge on Purchasing Products - Wahyu Annas; Misti Hariasih (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine the Effect of advertising, perceptions and consumer knowledge on product purchases at PT. Javas Tripta Mandala. The analytical tool used is tabulating the questionnaire, collecting data in the form of validity and reliability tests. The hypothesis in this study is the Effect of advertising, perceptions and knowledge of consumers on product purchases to test this hypothesis used multiple linear regression analysis tools.The results of the research instrument obtained based on the validity test showed that all questions in the questionnaire were declared valid. To test the reliability of all variables, the Cronbach’s Alpha value is obtained> 0.6, so it is declared reliable. Hypothesis testing based on the F test, t test and Adjusted R2 shows that there is a significant effect of advertising, perceptions and consumer knowledge on product purchases.